Gagasan Pemikiran Ekonomi Islam: Implementasi dan Usaha Pengembangannya - Nihayatul Maskuroh (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
A conception of the idea of Islamic economic thought which is implemented through the Islamic bankingsystem using the profit-sharing system applied to the interest-free banking system is one of the onlyelements of the Islamic economic system. Thus, when talking about the Islamic economic system, it isdiscussed is a hepotesis of an Islamic economic system that was applied in the era of the glory ofIslam.The idea of Islamic economic thinkers with all their efforts and efforts can be implementedsynergistically if supported by a strategic circle between the strong desire of the government as the policymaker (political will) and the socialization of the Islamic economic system itself and the implementationof the Islamic economic system as well – better